Anti-inflammatory effects of leptin and cholecystokinin on acetic acid-induced colitis in rats: role of capsaicin-sensitive vagal afferent fibers - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
Leptin and cholecystokinin (CCK) have a synergistic interaction in the suppression of food intake, and afford similar gastroprotective activity. The present study was designed to investigate the putative protective effects of CCK and leptin on acute colonic inflammation. Leptin or CCK-8s was injected to rats intraperitoneally immediately before and 6 h after the induction of colitis with acetic acid. CCK-A receptor antagonist (L-364,718) or CCK-B receptor antagonist (L-365,260) was injected intraperitoneally 15 min before leptin or CCK treatments. In a group of rats, vagal afferent fibers were denervated by topical application of capsaicin on the cervical vagi. Rats were decapitated at 24 h, and the distal 8 cm of the colon were removed for macroscopic scoring, determination of tissue wet weight index (WWI), histologic assessment and tissue myeloperoxidase (MPO) activity. All inflammation parameters were increased by acetic acid-induced colitis compared to control group. Leptin or CCK-8s treatment reduced these parameters in a similar manner, while co-administration of leptin and CCK was found to be more effective in reducing the macroscopic score and WWI. CCK-8s-induced reduction in the score and WWI was prevented by CCK-A, but not by CCK-B receptor antagonist, whereas neither antagonist altered the inhibitory effect of leptin on colitis-induced injury. On the other hand, perivagal capsaicin prevented the protective effects of both CCK-8s and leptin on colitis. Our results indicate that leptin and CCK have anti-inflammatory effects on acetic acid-induced colitis in rats, which appear to be mediated by capsaicin-sensitive vagal afferent fibers involving the reduction in colonic neutrophil infiltration. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: leptin; CCK; inflammation; vagal afferents; neutrophils; MPO; INDUCED GASTRIC-LESIONS; INTESTINAL INFLAMMATION; NITRIC-OXIDE; BODY-WEIGHT; LEAN MICE; EXPRESSION; RECEPTOR; GASTROPROTECTION; NEURONS; GENE